2012
DOI: 10.1177/0961203312437272
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of antiphosphatidylethanolamine antibodies in the diagnosis of the antiphospholipid syndrome

Abstract: The diagnosis of seronegative antiphospholipid syndrome (APS) has been proposed for patients with well-defined clinical APS but persistently negative for the routinely tested antiphospholipid antibodies (aPLs): antibodies to cardiolipin (aCL) and to b 2 glycoprotein I (ab 2 GPI) and lupus anticoagulant (LA). Antibodies directed to phosphatidylethanolamine (aPE) have been described as the sole aPLs in some patients with clinical manifestations of APS. Here, we briefly summarize the available data on the clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Even if aPE are higher in SLE [14] and in APS patients [20] than in controls, their titers are not correlated with other APLAs [20]. There are studies that have not found any correlations of the aPE with the clinical APS events [20], but other authors sustained a possible utility in seronegative APS [21].…”
Section: Discussionmentioning
confidence: 95%
“…Even if aPE are higher in SLE [14] and in APS patients [20] than in controls, their titers are not correlated with other APLAs [20]. There are studies that have not found any correlations of the aPE with the clinical APS events [20], but other authors sustained a possible utility in seronegative APS [21].…”
Section: Discussionmentioning
confidence: 95%
“…aPE has also been described in a subgroup of patients with clinical APS features, but without serological positive criteria APLAs; patients classified as "seronegative" APS. In these cases, non-criteria APLAs, including aPE, could be identified [18]. The results of studies regarding APLAs expression and significance in APS are divergent and one reason might be the lack of standardization of the laboratory determinations; so, efforts have been made in recent years to reach accuracy in the APS diagnosis [19].…”
Section: Discussionmentioning
confidence: 99%
“…The detection of aPE is still not very popular due to the lack of: 1. Suitable microtiter plate [ 26 , 27 ]; 2. Suitable buffer and constituents such as fetal calf serum, adult bovine serum, adult bovine plasma [ 26 , 27 ]; 3.…”
Section: Discussionmentioning
confidence: 99%
“…Suitable microtiter plate [ 26 , 27 ]; 2. Suitable buffer and constituents such as fetal calf serum, adult bovine serum, adult bovine plasma [ 26 , 27 ]; 3. Origin of PE – egg yolk, soybean, bovine brain, Escherichia coli [ 27 ]; 4.…”
Section: Discussionmentioning
confidence: 99%